An ontological proposal for representing the Open Science movement: proposed ontologically well-founded conceptual model (Advances in Knowledge Representation, 2023)
Open Science involves the scientific practice that defends that the entire research development process must be shared openly, from research results, data, codes, among others. Therefore, this summary will present an initial proposal for Open Science ontology, in order to organize knowledge and model this movement and its relationships. SABio was used as a technological input, and from the design stage of this software, OntoUML was used, a tool that implements the concepts of OntoClean. As a result, it was possible to take the first steps towards the construction of Open Science ontological modeling. It is considered that this product is still in its infancy and seeks to expand the relations of the complex scientific world that urges the need for freer access to research results, as well as, in the process, in scientific data and in the construction of these researches.